A Paal–Knorr Approach to 3,4-Diaryl-Substituted Pyrroles: Facile Synthesis of Lamellarins O and Q - Ramírez-Rodríguez, Armando; Méndez, José M.; Jiménez, Cristina C.; León, Fernando; Vazquez, Alfredo (Synthesis, 2012)
A very simple, yet efficient synthetic methodology, to obtain 3,4-diaryl-substituted pyrroles is described. The approach is based on the Knoevenagel condensation between arylacetonitriles and substituted aromatic aldehydes, followed by conjugate addition of cyanide to afford succinonitriles in excellent yields. The products thus obtained were subjected to DIBAL-H reduction, followed by cyclization under acidic conditions to produce the corresponding pyrroles in good overall yields. The utility of this protocol is exemplified by the synthesis of the marine alkaloids lamellarins O and Q.
Keywords: pyrroles; Paal–Knorr; lamellarins; heterocycles; natural products